The value of next-generation metagenomic sequencing in pathogen detection of pleural effusions and ascites from children with sepsis - Liu, Gang; Wang, Lijuan; Li, Xuming; Zhang, Ye; Long, Hu; Wang, Yi; Gao, Hengmiao; Xia, Han; Qian, Suyun (Frontiers in Cellular and Infection Microbiology, 2023)
Objective: To investigate the diagnostic value of metagenomic next-generation sequencing (mNGS) using pleural effusion and ascites from children with sepsis. Methods: In this study, children with sepsis or severe sepsis and appeared pleural or peritoneal effusions were enrolled, of whom the pleural effusions or ascites and blood samples were conducted pathogen detection using both conventional and mNGS methods. The samples were divided into pathogen-consistent and pathogen-inconsistent groups based on the consistency of mNGS results from different sample types, and into exudate and transudate groups based on their pleural effusion and ascites properties. The pathogen positive rates, pathogen spectrum, consistency between different sample types, and clinical diagnosis consistency were compared between mNGS and conventional pathogen tests. Results: A total of 42 pleural effusions or ascites and 50 other type samples were collected from 32 children. The pathogen positive rate of the mNGS test was significantly higher than that of traditional methods (78.57% vs. 14.29%, P < 0.001) in pleural effusion and ascites samples, with a consistent rate of 66.67% between the two methods. Nearly 81.82% (27/33) of mNGS positive results of the pleural effusions and ascites samples were consistent with clinical evaluation, and 81.82% (27/33) of these positive samples reported 1-3 pathogens. The pathogen-consistent group outperformed the pathogen-inconsistent group in terms of consistency with respect to clinical evaluation (88.46% vs. 57.14%, P = 0.093), while there was no significant difference between the exudate and transudate groups (66.67% vs. 50.00%, P = 0.483). Conclusion: Compared to conventional methods, mNGS has great advantages in pathogen detection of pleural effusion and ascites samples. Moreover, consistent results of mNGS tests with different sample types provide more reference values in clinical diagnosis.